2019
DOI: 10.1002/ejp.1331
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐related chronic pain: Investigation of the novel analgesic drug candidate cebranopadol in a randomized, double‐blind, noninferiority trial

Abstract: Background Cancer‐related pain is a growing health problem given the increasing life expectancy of cancer patients. Opioids are commonly used to treat cancer‐related pain, but carry the risk of severe side effects, limiting their use. Cebranopadol is a first‐in‐class drug candidate, combining nociceptin/orphanin FQ peptide and opioid peptide receptor agonism. This trial examined the analgesic efficacy of cebranopadol compared with morphine prolonged release (PR) in patients with moderate‐to‐severe cancer‐relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…The progressive ratio schedule of reinforcement was used to compare the reinforcing strengths of cebranopadol and fentanyl, which can differentiate reinforcing strengths of abused drugs that function as positive reinforcers. 6,35,36 The ratio progression of the progressive-ratio schedule was from 20 (first injection) to 25, then to 32,40,50,62,77,95,117,144,177,218,267,328, and finally 402 (15th injection). The operant response was maintained at 3 μg/kg per injection of oxycodone until the response was stable (mean ± three injections for three consecutive sessions).…”
Section: Drug Self-administrationmentioning
confidence: 99%
“…The progressive ratio schedule of reinforcement was used to compare the reinforcing strengths of cebranopadol and fentanyl, which can differentiate reinforcing strengths of abused drugs that function as positive reinforcers. 6,35,36 The ratio progression of the progressive-ratio schedule was from 20 (first injection) to 25, then to 32,40,50,62,77,95,117,144,177,218,267,328, and finally 402 (15th injection). The operant response was maintained at 3 μg/kg per injection of oxycodone until the response was stable (mean ± three injections for three consecutive sessions).…”
Section: Drug Self-administrationmentioning
confidence: 99%
“…Early clinical trials suggest safety and efficacy of Cebranopadol for a variety of pain conditions [40][41][42][43][44][45][46] (Table 1). Many of these investigations were designed to assess the tolerability of Cebranopadol and compare its pain mitigating effects against placebo.…”
Section: Development Of M and Nop Mixed Agonistsmentioning
confidence: 99%
“…Many of these investigations were designed to assess the tolerability of Cebranopadol and compare its pain mitigating effects against placebo. Although some studies incorporated conventional agents in some arms of the study, 41,43,45,46 the effectiveness of Cebranopadol was never directly compared with those conventional agents. 41,43,46 Some studies were limited by brief duration of investigation, 42,44 small samples, 40,45 and low retention rates.…”
Section: Development Of M and Nop Mixed Agonistsmentioning
confidence: 99%
“…In turn, some behavioral experiments have revealed that opioid-N/OFQ hybrids such as SR16435, which behaves as a mixed MOP–NOP receptor partial agonist [ 260 ], are highly promising analgesics for the treatment of acute and even neuropathic pain, devoid of respiratory depression [ 261 ]. For example, a mixed opioid/NOP agonist, cebranopadol, is in early phase clinical development in treating diabetic neuropathy, cancer pain, and lower back pain [ 262 , 263 , 264 ].…”
Section: Anti-opioid Peptides: Potential Therapeutic Interestmentioning
confidence: 99%